Rhamnolipid from Pseudomonas aeruginosa can improve the removal of Direct Orange 2GL in textile dye industry effluents - da Silva, Vinicius Luiz [UNESP]; Dilarri, Guilherme [UNESP]; Mendes, Carolina Rosai [UNESP]; Lovaglio, Roberta Barros; Gonçalves, Adilson Roberto [UNESP]; Montagnolli, Renato Nallin; Contiero, Jonas [UNESP] (Elsevier, 2021)
Rhamnolipids are a class of glycolipid biosurfactants with several applications, including the bioremediation of pollutant substances. However, little is known about its application in the treatment of textile effluents. Therefore, this work aims to apply a rhamnolipid-type biosurfactant to improve the sorption of the Direct Orange 2GL textile dye. The adsorption isotherms, kinetics, and thermodynamics were investigated from a novel approach. The adsorbate/adsorbent ratio was also characterized by FT-IR spectroscopy. Bioassays using Daphnia similis verified changes in toxicity after the dye underwent the proposed treatment. The adsorption dataset was better adjusted to the Langmuir model, which indicated a strong chemical interaction coming from a finite number of binding sites. The adsorption was only possible at acidic pH. Kinetic studies further demonstrated that the adsorption equilibrium is achieved in 60 min when 1.181 μg mg−1 of dye was adsorbed by the adsorbent. Thermodynamics showed that the adsorption process was proportionally influenced by higher temperatures. The thermodynamics studies also showed a spontaneous and endothermic sorption process. The FT-IR spectroscopy identified the adsorbate/adsorbent binding sites, proving that the bond between the dye and rhamnolipid occurred through the hydrogen bonds. The recovery of both dye and rhamnolipid after the adsorption was also efficient, as more than 50% of the adsorbed dye was recovered. The post-treatment bioassays using D. similis found a significant decrease in toxicity, yielding less than 30% mortality rate after adsorption. It is concluded that the rhamnolipid was an effective adsorbent and it is a viable component to treat effluents containing textile dyes.
Keywords: Bioassay; Biosurfactant; Daphnia similis; Isotherms; Toxicity